The system of rice intensification (SRI). Contributing to food security, competitiveness, and resilience by adapting SRI to local contexts. - Centro de Gestión del Conocimiento y Cooperación Horizontal (CGCCH) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The System of Rice Intensification (SRI) is a project that seeks solutions to enhance the resilience of rice systems to climate change, increase their productivity and competitiveness, and reduce greenhouse gas emissions. SRI addresses these challenges through an integrated approach that changes the management of plants, soil, water, and nutrients to improve productivity and resilience while reducing greenhouse gas emissions. This approach leverages system innovations at the local level and helps reduce the vulnerability of rice producers to the biophysical and socio-economic impacts of climate change.